PENGARUH EVENT MARKETING HAPPY SUNDAY TERHADAP BRAND IMAGE SAYAP MAS PADA CV.ULUL AZMI SULAIMAN - Sholichah, Nadiatus; Istiani, Istiani; Azwar, M Yusuf (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Cigarettes are one of the industries in Indonesia that experiences an increase every year. To achieve company goals, every company uses promotional strategies. One of the promotions used is event marketing. Marketing events carried out by the company must also be right on target, so that they can improve the company's brand image. One of them is carried out by CV. Ulul Azmi Sulaiman to improve the brand image of Sayap Mas cigarettes. The purpose of this activity is to determine the influence of event marketing on the brand image of Sayap Mas cigarettes